Oral health status and interventions for internally displaced people living in a camp-like setting in North-Central Nigeria - Ohiaeri, Anoziem Anozie (Orapuh Journal, 2025)
Introduction The conflict in North-Eastern Nigeria, which has lasted for over a decade and has been compounded by communal clashes and natural disasters, has resulted in the highest number of internally displaced persons (IDPs) in the West-Central African subregion. While oral health is integral to overall well-being, it is often overlooked in humanitarian interventions targeting IDPs. Purpose This study underscores the importance of oral health in the overall health of IDPs, advocating for its inclusion in intervention programs for this vulnerable population. The findings may also inform strategies for addressing oral health challenges among other at-risk groups. Methods This study analysed secondary data from a convenience sample of 119 individuals residing in an IDP camp in North-Central Nigeria who participated in a dental health outreach. Ethical approval was obtained from the Ethics Committee of Anglia Ruskin University, and camp authorities granted permission for treatment and data collection. Data were processed using SPSS (V.28.0.1.0 [142]), exploring associations between demographic factors, oral hygiene practices, access to dental care, and dental indices (OHI-S and DMFT). The original dataset facilitated immediate care provision during the outreach. Results The overall oral hygiene status of participants was fair, with a mean OHI-S score of 2.46. Age was significantly associated with OHI-S (p < 0.001). The prevalence of dental caries was 32.8%, with a mean DMFT score of 1.11 and an unmet treatment need of 93%. A significant association was found between prior contact with dental services and DMFT (p < 0.001). Although 90.8% of participants reported using a toothbrush, only 41.7% brushed their teeth at least twice daily. Access to dental care was notably poor, with 84% of participants reporting no previous contact with dental services. Despite a fair assessment of oral health status, the substantial unmet treatment need remains a major concern. Conclusion The findings highlight significant oral health disparities among IDPs in camp-like settings, particularly regarding disease burden and inadequate access to dental care. Addressing these challenges requires urgent oral health policy interventions, including community-based outreach programs and direct access to essential oral healthcare services. Additionally, promoting effective oral hygiene practices among IDPs is crucial for improving their overall health outcomes.